(untitled) (International Journal of Engineering Management Science, 2024)
This review paper presents an overview of the experimental studies conducted on concrete reinforced with polyvinyl alcohol (PVA) fibers. Polyvinyl alcohol fibers have gained significant attention as a reinforcement material in concrete due to their high tensile strength, excellent bonding with cementitious matrices, and resistance to various environmental factors. The paper begins with a discussion on the properties of PVA fibers and their advantages in concrete reinforcement. Subsequently, previous studies on the use of PVA fibers in concrete reinforcement are reviewed, with a focus on their effects on mechanical properties such as compressive strength, tensile strength, and flexural strength, as well as durability properties including freeze-thaw resistance and chloride ion penetration resistance. The methodology employed in experimental studies, including mix design, fiber type and dosage, and testing methods, is described. The results of these experimental studies are presented, highlighting the improvements in mechanical and durability properties achieved by incorporating PVA fibers in concrete. Finally, conclusions drawn from the reviewed studies are discussed, along with recommendations for future research in this area.